Legal Analysis of the Crime of Sexual Intercourse Against a Child by a Stepfather (Decision Study Number 13/Pid.Sus/2023/PN Wgw) - Saritma, Yogi Witma; Faisal Abdaud; Rahim, Abdul Jabar (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Children must be protected from all sorts of cruel treatment that lead to violations of human rights since they are the future generation of the country and are its buds, potential, and young people. Children that get harsh treatment will never grow or develop in the future. In Indonesia, instances involving the inhumane treatment of children are common. Case number 13/Pid.Sus/2023/PN Wgw is one such case that is pending at the Wangi-Wangi District Court. This case involves the stepfather (DEFENDANT LL) engaging in illicit sexual relations with a minor (CHILD VICTIM A). Whether the judge's decision to charge the defendant with a crime was in line with the law at hand is the wording of the research problem. Furthermore, how is the case Number 13/Pid.Sus/2023/PN Wgw analyzed using the theories of ratio decidendi and child protection? Using both a statutory and a case approach, this research methodology is normative. The Judge Panel in case number 13/Pid.Sus/2023/PN Wgw sentenced DEFENDANT LL in conformity with the law that was in effect at the time. dependent on the first alternative indictment article's definition of a criminal act, this is dependent on all of those components being met. Based on a child protection theory analysis of case number 13/Pid.Sus/2023/PN Wgw, it can be concluded that defendant LL's acts have stunted the physical, mental, and social development of child victim A. Meanwhile, the judges have examined the facts based on the evidence presented during the trial, applying the Ratio Decidendi Theory. As a result, they are confident in declaring that DEFENDANT LL has been legally and credibly proven to have committed a criminal act against CHILD VICTIM A.